Whole-farm Model: Detailed Data on Nine Farms for Impact Assessment of Africa RISING Technologies - Wageningen University and Research; International Institute of Tropical Agriculture (International Food Policy Research Institute, 2018)
The zip.file contains the Farm DESIGN model (software) as well as the input data. A user manual of the software is available online (https://sites.google.com/site/farmdesignmodel/download). The zipped Farm DESIGN model contains the whole-farm representation of nine farms in Northern Ghana. A low, medium and a high resource endowed farm per site, namely in Duko (Northern Region), Nyangua (Upper East) and Zanko (Upper West). There are several models per farm: 1. The current/ actual farm configuration 2. The baseline (reset to a situation with traditional (no Africa RISING) farming practices) 3. The farm, where Africa RISING Package 1 (Maize) is implemented 4. The farm, where Africa RISING Package 2 (Cowpea) is implemented 5. The farm, where Africa RISING Package 3 (Soybean) is implemented 6. The farm, where Africa RISING Package 4 (Maize-Legume Rotation) is implemented 7. The farm, where Africa RISING Package 5 (Maize-Legume Strip Crop) is implemented 8. A farm-model that is ready for an exploration (containing additional options the model may choose)